2017
DOI: 10.1089/ars.2016.6905
|View full text |Cite
|
Sign up to set email alerts
|

Mito-Apocynin Prevents Mitochondrial Dysfunction, Microglial Activation, Oxidative Damage, and Progressive Neurodegeneration in MitoPark Transgenic Mice

Abstract: Collectively, our data demonstrate, for the first time, that a novel orally active apocynin derivative improves behavioral, inflammatory, and neurodegenerative processes in a severe progressive dopaminergic neurodegenerative model of PD. Antioxid. Redox Signal. 27, 1048-1066.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 77 publications
2
125
0
Order By: Relevance
“…The large energetic demand along with dopamine metabolism generate high basal levels of reactive oxygen species, suggesting that added oxidative stress from mitochondrial dysfunction could be especially damaging . Indeed, dopamine neurons from MitoPark mice exhibit increased markers of oxidative stress as well as altered morphology in nigral microglia indicative of neuroinflammation . Furthermore, dopamine neurons in MitoPark mice exhibit structurally altered mitochondria that are associated with the intracellular protein aggregates observed with this model .…”
Section: Discussionmentioning
confidence: 95%
“…The large energetic demand along with dopamine metabolism generate high basal levels of reactive oxygen species, suggesting that added oxidative stress from mitochondrial dysfunction could be especially damaging . Indeed, dopamine neurons from MitoPark mice exhibit increased markers of oxidative stress as well as altered morphology in nigral microglia indicative of neuroinflammation . Furthermore, dopamine neurons in MitoPark mice exhibit structurally altered mitochondria that are associated with the intracellular protein aggregates observed with this model .…”
Section: Discussionmentioning
confidence: 95%
“…493,494 Also, the short-chain homolog, Mito-Apo 2 , was shown to be safe and neuroprotective in mice treated daily via oral gavage for 12 days at the dosage of 3 mg/kg. 495 …”
Section: Mitochondria-targeted Therapeutics In the Pre-clinical Momentioning
confidence: 99%
“…In our study, we observed that quercetin showed only a modest protective effect in MitoPark mice, possibly because of the fact that the MitoPark mouse is the most severe model of PD. Indeed, although the MitoPark model has been used since 2007 to test the efficacy of various interventions, only a few compounds have shown neuroprotective effects in MitoPark mice (Langley et al, 2017, Marcellino et al 2010. MitoPark mice show changes in electrophysiological parameters and dopamine signaling, even prior to 12 weeks when the onset of motor symptoms occurs (Good et al 2011;Branch et al 2016), which is when we started treating the animals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that quercetin showed only a modest protective effect in MitoPark mice, possibly because of the fact that the MitoPark mouse is the most severe model of PD. Indeed, although the MitoPark model has been used since 2007 to test the efficacy of various interventions, only a few compounds have shown neuroprotective effects in MitoPark mice (Langley et al .,, Marcellino et al . , Smith et al .…”
Section: Discussionmentioning
confidence: 99%